FutureMS cohort profile: a Scottish multicentre inception cohort study of relapsing-remitting multiple sclerosis. Issue 6 (29th June 2022) - Kearns, Patrick K A; Martin, Sarah J; Chang, Jessie; Meijboom, Rozanna; York, Elizabeth N; Chen, Yingdi; Weaver, Christine; Stenson, Amy; Hafezi, Katarzyna; Thomson, Stacey; Freyer, Elizabeth; Murphy, Lee; et al.
Abstract : Purpose: Multiple sclerosis (MS) is an immune-mediated, neuroinflammatory disease of the central nervous system and in industrialised countries is the most common cause of progressive neurological disability in working age persons. While treatable, there is substantial interindividual heterogeneity in disease activity and response to treatment. Currently, the ability to predict at diagnosis who will have a benign, intermediate or aggressive disease course is very limited. There is, therefore, a need for integrated predictive tools to inform individualised treatment decision making. Participants: Established with the aim of addressing this need for individualised predictive tools, FutureMS is a nationally representative, prospective observational cohort study of 440 adults with a new diagnosis of relapsing-remitting MS living in Scotland at the time of diagnosis between May 2016 and March 2019. Findings to date: The study aims to explore the pathobiology and determinants of disease heterogeneity in MS and combines detailed clinical phenotyping with imaging, genetic and biomarker metrics of disease activity and progression. Recruitment, baseline assessment and follow-up at year 1 is complete. Here, we describe the cohort design and present a profile of the participants at baseline and 1 year of follow-up. Future plans: A third follow-up wave for the cohort has recently begun at 5 years after first visit and a further wave of follow-up is funded for year 10. Longer-term follow-up is anticipated thereafter.